2017
DOI: 10.1177/0018578717715352
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Pharmacist Market Perceptions: Comparison of Critical Care Program Directors and Directors of Pharmacy

Abstract: While hospital beds continue to decline as patients previously treated as inpatients are stabilized in ambulatory settings, the number of critical care beds available in the United States continues to rise. Growth in pharmacy student graduation, postgraduate year 2 critical care (PGY2 CC) residency programs, and positions has also increased. There is a perception that the critical care trained pharmacist market is saturated, yet this has not been evaluated since the rise in pharmacy graduates and residency pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Unlike in the USA [ 34 ], the UK does not yet have a recognised critical care pharmacist training programme. The need for [ 35 ], and format of [ 9 ], an advanced-level training programme for critical care pharmacists has been identified, but national delivery and credentialling remains a challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in the USA [ 34 ], the UK does not yet have a recognised critical care pharmacist training programme. The need for [ 35 ], and format of [ 9 ], an advanced-level training programme for critical care pharmacists has been identified, but national delivery and credentialling remains a challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Two separate national survey studies described job market perceptions among RPDs and directors of pharmacy in PGY2 CC and EM residency programs, respectively. 8,9 Each clinical pharmacy specialty has its own job market that cannot be directly compared. The studies also reported post-residency job obtainment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study differs from previous examples in its focus and survey audience. Two separate national survey studies described job market perceptions among RPDs and directors of pharmacy in PGY2 CC and EM residency programs, respectively 8,9 . Each clinical pharmacy specialty has its own job market that cannot be directly compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations